2015
DOI: 10.1063/1.4935545
|View full text |Cite
|
Sign up to set email alerts
|

Controlling length-scales of the phase separation to optimize organic semiconductor blends

Abstract: The length-scale of phase separation in organic semiconductor donor-acceptor mixtures, while being crucially important for applications, is a non-trivial parameter to control in non-equilibrium thin film growth. We present a comprehensive study of all the important parameters that can be used to tailor the length-scale of phase separation in organic semiconductor mixtures. We employed different substrate temperatures, different growth rates, time-dependent deposition rates, and surface functionalization layers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…The three mixtures studied (Fig. 2g-i) exhibit nano phase separation into pure domains dependent on the growth conditions [44,[46][47][48]. For DIP:C60 and 6T:C60 and mixing ratios deviating from 1:1, we observe smaller roughness values compared to the pure compounds, induced due to larger disorder and therefore smaller step edges as described above.…”
Section: E Impact Of Co-crystal Formationsupporting
confidence: 58%
“…The three mixtures studied (Fig. 2g-i) exhibit nano phase separation into pure domains dependent on the growth conditions [44,[46][47][48]. For DIP:C60 and 6T:C60 and mixing ratios deviating from 1:1, we observe smaller roughness values compared to the pure compounds, induced due to larger disorder and therefore smaller step edges as described above.…”
Section: E Impact Of Co-crystal Formationsupporting
confidence: 58%
“…After having demonstrated the strong effect of Q π on the energy levels in model systems based on ZnPc derivatives, we further analyse its impact in donor:acceptor blends which are typically used in OSCs. Such blended structures usually exhibit significant structural disorder and phase separation that both can change with mixing ratio 13,32,35,36 . Previous studies found changes of energy levels with donor:acceptor mixing ratio, which were assigned to changes in crystal size and to electrostatic changes 13,15,37 .…”
Section: Resultsmentioning
confidence: 99%
“…The reason for this might be that a more shallow surface potential landscape exists due to the underlying organic layer that leads to larger diffusion lengths of the molecules and therefore fewer, but larger islands. 60 The observed continuous filling of the single layers leading to very smooth films might be explained by the C 60 filling the voids between the DIP crystallites. Besides an overall increase of D island with film thickness, an interesting intra-layer behavior of D island is observed.…”
Section: Discussionmentioning
confidence: 99%